2009
DOI: 10.1007/bf03324916
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Prevention of hip fractures by exposure to sunlight and pharmacotherapy in patients with Alzheimer’s disease

Abstract: The present study clarified the efficacy of three interventions, including exposure to sunlight, menatetrenone, and risedronate with calcium and/or vitamin D supplementation against hip fractures in patients with Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…We also found that unreliable data was one of the most important reasons for the retraction, involving more than one fourth of the retracted SRs, and some SRs had included retracted primary studies [42][43][44] . SRs have the potential to provide sufficient sample size to make more powerful evidence-based conclusions than primary studies.…”
Section: Results In Relation To Prior Studiesmentioning
confidence: 88%
“…We also found that unreliable data was one of the most important reasons for the retraction, involving more than one fourth of the retracted SRs, and some SRs had included retracted primary studies [42][43][44] . SRs have the potential to provide sufficient sample size to make more powerful evidence-based conclusions than primary studies.…”
Section: Results In Relation To Prior Studiesmentioning
confidence: 88%
“…We also found that unreliable data was one of the most important reasons for the retraction, involving more than one fourth of the studies, and some SRs had included retracted primary studies [40][41][42] . SRs have the potential to provide su cient sample size and generalizable population information to make more powerful evidence-based conclusions.…”
Section: Discussionmentioning
confidence: 89%
“…We also found that unreliable data was one of the important reasons for the retraction, involving more than one fourth of the studies, and some SRs included retracted primary studies [39-41] . SRs have the potential to provide sufficient sample size and generalizable population information to make more powerful evidence-based conclusions.…”
Section: Discussionmentioning
confidence: 99%